Queenship at the Renaissance courts of Britain : Catherine of Aragon and Margaret Tudor, 1503-1533 - Beer, Michelle L. (Royal Historical Society studies in history. New series., 2018)
A study of the performance of queenship by two Tudor monarchs, showing the strategies they used to assert their power.